2023
DOI: 10.5808/gi.22072
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic biomarkers and molecular pathways mediating Helicobacter pylori–induced gastric cancer: a network-biology approach

Abstract: Cancer of the stomach is the second most frequent cancer-related death worldwide. The survival rate of patients with gastric cancer (GC) remains fragile. There is a requirement to discover biomarkers for prognosis approaches. Helicobacter pylori in the stomach is closely associated with the progression of GC. We identified the genes associated with poor/favorable prognosis in H. pylori–induced GC. Multivariate statistical analysis was applied on the Gene Expression Omnibus (GEO) dataset GSE54397 to identify di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 165 publications
0
2
0
Order By: Relevance
“…Multiple genes are associated with gastric tumorigenesis [ 17 , 18 ]. In an effort to identify the genes responsible for the tumorigenesis of GC, we performed a genome-wide gene expression analysis of human GC and adjacent normal tissues from 27 Korean GC patients (NCBI GEO accession GSE30727) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple genes are associated with gastric tumorigenesis [ 17 , 18 ]. In an effort to identify the genes responsible for the tumorigenesis of GC, we performed a genome-wide gene expression analysis of human GC and adjacent normal tissues from 27 Korean GC patients (NCBI GEO accession GSE30727) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that eradicating H. pylori in infected asymptomatic individuals of all ages can reduce the occurrence of gastric cancer (YU et al, 2023;KAMAREHEI et al, 2023). Antibiotic therapy is the most effective and widely used treatment for H. pylori infection, in which clarithromycin, amoxicillin, or metronidazole can inhibit H. pylori infection (GODERSKA et al, 2018).…”
Section: Introductionmentioning
confidence: 99%